An Arthropod Hormone, Ecdysterone, Inhibits the Growth of Breast Cancer Cells via Different Mechanisms - Shuvalov, O.; Fedorova, O.; Tananykina, E.; Gnennaya, Y.; Daks, A.; Petukhov, A.; Barlev, N. A. (Frontiers in Pharmacology, 2020)
Ecdysterone (Ecdy) is a hormone found in arthropods, which regulates their development. It is also synthesized by a number of plants to combat insect pests. It provides a number of beneficial pharmacological effects including the anabolic and adaptogenic ones. Ecdysterone is widely marketed as food supplement to enhance the physical performance of athletes. In addition to the estrogen receptor beta (ERbeta)-dependent anabolic effect of Ecdy in muscles, the molecular mechanisms of the plethora of other Ecdy-induced pharmacological effects remain unknown. The aim of this study was to investigate the pharmacological effect of ecdysterone on human breast cancer cell lines of different molecular subtypes. Surprisingly, in contrast to the anabolic effect on muscle tissues, we have revealed a tumor suppressive effect of Ecdy on a panel of breast cancer cell lines studied. Using the SeaHorse-based energy profiling, we have demonstrated that Ecdy dampened glycolysis and respiration, as well as greatly reduced the metabolic potential of triple negative breast cancer (TNBC) cell lines. Furthermore, we have revealed that Ecdy strongly induced autophagy. As part of the combined treatment, based on the Combination Index (CI) and Dose Reduction Index (DRI), Ecdy synergized with doxorubicin to induce cell death in several breast cancer cell lines. In contrast, Ecdy had only minor effect on non-transformed human fibroblasts. Collectively, our results indicate that ecdysterone can be considered as a new potential adjuvant for genotoxic therapy in treatment of breast cancer patients.